Люди, которые всегда со мной - Абгарян Наринэ Юрьевна (АСТ, 2016)
Экземпляры: ф.2 (20221212) / Инвентарный номер: 62951 / Цена: / Сис.шифр: 84(2Рос=Рус)6-4 / Авт.знак: А 13 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6-44